Design of dual octagonal ring elements for broadband and high gain reflectarray antenna - Bharati R.; Ajitesh; Dubey R.; Meshram M.K. (My University, 2025)
A single-layer reflectarray with the periodicity of γ/2(@12 GHz) is designed. An octagonal-shaped two concentric ring is designed as a unit cell which is used for better bandwidth and phase characteristics. The phase of 540 degrees is obtained by adjusting the length of the segment. The minimum space between the two cells is γ/2. The reflectarray is designed for high gain, high aperture efficiency, and broadband characteristics. A reflectarray of diameter 204mm is designed on a circular aperture. It consists of 156 elements The aperture efficiency obtained is 65.3%. The method involved for phase compensation is the variable size method. The reflector is center fed using a pyramidal horn antenna. The gain of the reflectarray in the broadside direction is 25.3 dBi. The 1-dB Gain Bandwidth obtained is 18.3% (11.2 - 13.6 GHz). Many simulations are performed for the Ku band for use in satellite communication The design is a compact size, broadband, high gain with high aperture efficiency. The side lobes are also suppressed and is 14.9 dB below the main lobe. © 2022 IEEE.